The latest results from the technological and typological analysis of chipped stone assemblages from Ilipinar, Pendik, Fikir tepe and Menteş, NW Turkey - Gatsov, Ivan (Documenta Praehistorica, 2003)
The papers presents the latest results from the technological and typological analysis of chipped stone assemblages from Ilipinar, Pendik, Fikir tepe, and Mentese in NW Turkey. The stone industry of Ilipinar shows parallels with the chipped stone material from Fikir tepe. At Ilipinar the period of technological and raw material changes in Bulgarian Thrace correspond to the end of phase V-A and to the whole V-B, but the technological and typological features are completely different.
Keywords: archaeology; arheologija; neolitik; kameno orodje; Turčija; Turkey; technology; tehnologija; tipologija